Contemporary Photography in Iran - Mohamadi, Aram. author. (orcid)0009-0003-5586-7146 Link aut Link
XVII, 214 p. 51 illus., 26 illus. in color.
Keywords: This book deals with Iranian photography from its first photography exhibition in 1964 until the present. Taking an interpretive-historical approach, this book will explain how photographic images in a particular context respond to the socio-political, technological, educational, and other determinants of the time, uncovering the internal logic of the evolution of the language of photographic images. Specifically, the book explores how these Iranian images and artworks have challenged traditional photographic conventions, defamiliarizing them, and how the perception of reality through the lens of photography has evolved in conjunction with changing conditions and perspectives. Aram Mohamadi is a photography critic, holding a bachelor's degree in photography, a master's degree, and a PhD in art studies. Since 2023, he has been serving as an Assistant Professor of Photography at the University of Kurdistan, Iran. His teaching responsibilities encompass photography studio and visual art criticism. His research primarily revolves around contemporary photography in Iran, with a specific emphasis on art photography.